A novel cocrystal explosive NTO/TZTN with good comprehensive properties1. Issue 36 (23rd April 2015) - Wu, Jin-Ting; Zhang, Jian-Guo; Li, Tong; Li, Zhi-Min; Zhang, Tong-Lai
<x xml:space="preserve">Abstract</x> A novel binary cocrystal explosive of NTO was discovered and it exhibits strong intermolecular hydrogen bond interaction in crystal structure.